The Implementation of Using Whatsapp and Youtube in FLTM Class: Teacher’s Perception - Desi Zabidin; Titin Rahmiatin; Rahmat Nasrullah (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Muhhammadiyah kendari, 2021)
This study focuses on teacher’s perception on the implementation of usingWhatsapp and Youtube at FLTM class at English Department, MuhammadiyahUniversity Kendari since teacher’s perception has not been investigated thoroughly inthe earlier research on the implementation of using WhatsApp and Youtube media as alearning tools. The objective of this study is to find out the teacher’s perception on theimplementation of using Whatsapp messanger and Youtube in class B 5t h semesters ofFLTM classroom at Muhammadiyah University students of Kendari . This studyemploys qualitative study design to find out lecturer’s perception in teaching processusing Whatsapp and Youtube. The instruments used in this study are documentati onand interview and the data are analyzed using data reduction, data display, meaningcoding, meaning condensation, meaning interpretation, conclusion drawing and datatriangulation. The findings reveal that the teacher considered to implement Whatsappand Youtube in teaching have several advantages and disadvantages in learningobjective and outcomes. This can be viewed in the arrangement of knowledge of subjectmatter, teacher-students interaction, design of instruction, and course management.Furthermore, teacher’s beliefs in using whatsapp and youtube in teaching appeared to bestrongly connected to the flexibility of teaching and learning process and learningcontent availability.